Crack-assisted charge injection into solvent-free liquid organic semiconductors via local electric field enhancement - Kim, Kyoung Hwan; Park, Myung June; Kim, Ju Hyung (Materials, 2020)
Non-volatile liquid organic semiconducting materials have received much attention as emerging functional materials for organic electronic and optoelectronic devices due to their remarkable advantages. However, charge injection and transport processes are significantly impeded at interfaces between electrodes and liquid organic semiconductors, resulting in overall lower performance compared to conventional solid-state electronic devices. Here we successfully demonstrate efficient charge injection into solvent-free liquid organic semiconductors via cracked metal structures with a large number of edges leading to local electric field enhancement. For this work, thin metal films on deformable polymer substrates were mechanically stretched to generate cracks on the metal surfaces in a controlled manner, and charge injection properties into a typical non-volatile liquid organic semiconducting material, (9-2-ethylhexyl)carbazole (EHCz), were investigated in low bias region (i.e., ohmic current region). It was found that the cracked structures significantly increased the current density at a fixed external bias voltage via the local electric field enhancement, which was strongly supported by field intensity calculation using COMSOL Multiphysics software. We anticipate that these results will significantly contribute to the development and further refinement of various organic electronic and optoelectronic devices based on non-volatile liquid organic semiconducting materials.
Keywords: Comsol multiphysics; Cracked structures; Local electric field; Organic electronics; Organic semiconducting materials; Polymer substrate; Solid state electronic devices; Transport process; Charge injection; Crack engineering; Liquid semiconductors; Organic electronics; Surface engineering